Online Education of Clean and Healthy Living Behavior (PHBS) in Overcoming the Spread of SARS COV-2 Virus for Gandul Cinere Village Health Cadre - Pramono, Andri Pramesyanti; Safira, Lisa; Yulianti, Retno; Nasrullah, Nanang; Rahmadika, Novri (Journal of Innovation and Community Engagement, 2022)
Gandul Cinere village is located bordered by South Jakarta. Jakarta has a fairly high number of SARS-COV 2 positive patients. The Indonesian Government has determined that Indonesia is entering the New Normal era in June 2020. Many people in the community do not care about health protocols in the New Normal era and consider that the Covid-19 pandemic is no longer a threat. Our goals are (1) increasing PHBS knowledge and awareness of health cadres to implement PHBS and to teach the community in everyday life in the New Normal era, and (2) decreasing incidence of Covid-19 related illness in Gandul Cinere Village. Therefore, a continuous understanding of health protocols is needed. PHBS is part of the health protocol that must be run in this New Normal era. Continued knowledge provision is required in order to prevent the transmission of Covid-19, especially in the Gandul Village area, Cinere, which borders the red zone area of Covid-19. Health cadres who are the vanguard need assistance and guidance in understanding and applying PHBS in everyday life. The methods used were online counseling, online discussion, online mentoring, and pre-/post-test implementation. The result showed increased knowledge about Clean and Healthy Living Behavior after given counseling and discussion with the respondent.